Managing new and remanufactured products with remanufacturing degree under patent protection. Issue 3 (22nd May 2019) - Cao, Xiaogang; Wang, Xianjia; Wen, Hui
Abstract : Purpose: This paper aims to propose a two-period model, including an original manufacturer, a retailer and a third-party remanufacturer, in which the products manufactured by the original manufacturer are patent-protected and the remanufacturing degree of remanufactured products influences the purchasing decisions of consumers. Design/methodology/approach: This paper analyzes the decisions of the original manufacturer, the retailer and the third-party remanufacturer of two periods, using Stackelberg game and obtains the equilibrium solutions of the three parties. Findings: The study finds that consumers' focus degree to the remanufacturing degree has a negative correlation with the equilibrium unit patent-licensing fee, the retail price of remanufactured products, the remanufacturing degree of remanufactured products and the wholesale price of new products in the first period, but has a positive correlation with the retail price of new products in the second period. Originality/value: (1) Consumers' focus degree to the remanufacturing degree has a negative correlation with the equilibrium unit patent-licensing fee, the retail price of remanufactured products, the remanufacturing degree of remanufactured products and the wholesale price of new products in the first period, but has a positive correlation with the retail price of new products in the second period. (2) The remanufacturing action efficiency of the third-party remanufacturer has a positive correlation with the equilibrium unit patent-licensing fee, the retail price of remanufactured products, the remanufacturing degree of remanufactured products and the wholesale and retail prices of new products in the second period.